PENGGUNAAN SANDAL KHUSUS UNTUK PENCEGAHAN KEAUSAN BATU CANDI BOROBUDUR - Brahmantara Brahmantara (Borobudur, 2022)
The use of mass tourism has several negative impacts on the preservation of Borobudur Temple. One of them is the condition of wear and tear on the stone stairs and floors. From the survey results and calculation of the percentage of stone wear of Borobudur Temple on the west and north side of the stone stairs are 63.39% and 27.84%, while on the south side stone stairs are 30.96%. One of the efforts to minimize wear and tear is the use of special sandals. This particular sandal study aims to obtain a prototype of footwear (sandals) that meet the criteria for durability, ergonomics and visual harmony (DEKS), as well as an effort to increase community participation through empowering local MSMEs (Micro, Small and Medium Enterprises). The research method went through two stages, namely: laboratory testing of sandal material samples, and the manufacture of special sandals. The results of the study concluded that the use of sandals can have an effect on efforts to prevent an increase in the power of the temple stones on the stairs and floors. Friction test results show that the type of sponge material has a lower level of hardness than the type of stone sponge, so it has a low impact on wear. Based on the criteria required in the formulation of the problem, the prototype design is made in three types, namely; prototypes I, II and III. This particular sandal is designed with the brand “Upanat Barabudur”. Taken from the inscription on the relief of Karmawibhangga panel 150 which means 'footwear'. Viewed from the perspective of historical and philosophical values, the use of special footwear is useful in an effort to minimize wear and tear and as a conservation education medium for visitors.